Do-Gooders at the End of Aid Scandinavian Humanitarianism in the Twenty-First Century - de Bengy Puyvallée, Antoine; Bjørkdahl, Kristian (Social Sciences, 2021)
Scandinavian countries are considered exceptional for their commitment to development cooperation, peace mediation, and humanitarian action. This book argues that policymakers can and do capitalize on this reputation to legitimize policy interventions and ideas.vThis title is also available as Open Access on Cambridge Core.